The clinician's guide to consulting : achieving performance change, desired outcomes, and staff acceptance - Reid, Dennis H. (Charles C Thomas, Publisher, Ltd., 2020)
"Clinicians who work with human service agencies often function in a consulting capacity with agency staff. Some clinicians work independently, and many others are employed within an agency. This book describes how clinicians can effectively change staff performance in the human services to promote implementation of consultative recommendations for the betterment of agency clients. The content is based on over five decades of behavior analytic research and application, and the experiences of clinicians who have demonstrated consistent success in consulting with a wide variety of human service agencies. The book is structured into four sections, each of which corresponds to various consulting strategies. Section I presents an introduction to the clinician's guide to consulting, achieving performance change and staff acceptance, outcome management in approach to consulting, and the underlying considerations for consulting success. Section II explores the specific strategies for promoting performance change and staff acceptance, consulting outcomes and expectations, training staff to carry out consultative recommendations, monitoring performance and outcome attainment, supporting proficient staff performance, and correcting nonproficient staff performance. Section III focuses on achieving consulting success during difficult situations, promoting job security, overcoming motivational issues among staff, self-motivation, and financial success. Section IV provides a list of Selected Readings containing numerous useful resources that cover the business side of consulting. This book is designed to help clinicians perform consulting duties effectively and acceptably"--